Prevalência de sobrepeso e obesidade em alunos de escolas privadas do município de presidente Prudente - SP - Fernandes, Rômulo Araújo [UNESP]; Kawaguti, Sandra Satie [UNESP]; Agostini, Lucas [UNESP]; de Oliveira, Arli Ramos; Ronque, Enio Ricardo Vaz [UNESP]; Freitas Júnior, Ismael Forte [UNESP] (My University, 2007)
The objective of this study was to describe the prevalence of overweight and obesity among schoolchildren attending private schools in the town of Presidente Prudente, SP, Brazil. The sample comprised 1,215 male and female students with an age range of 10 to 17 years. Body mass and height measurements were evaluated. Nutritional status was identified by means of Body Mass Index and the international table of reference values proposed by Cole et al.12 Data are represented in the form of means, standard deviations and frequencies. The Chi-square test was used to compare frequencies and Student's t test was applied to and means. P values below 5% were considered statistically significant and all statistical analysis were performed using SPSS 10.0 dedicated software. The observed prevalence rate of overweight and obesity was 35.7% for males, 20% for females (p = 0.001) and 28.6% for the whole sample. Therefore, this study concludes that the high overweight and obesity rates observed among students from the town of Presidente Prudente, particularly among the male sex, should be seen as a warning and indicate the need for interventions by health professional in the school environment.
Prevalence of overweight and obesity among students at private schools in Presidente Prudente, SP, Brazil
Keywords: Obesity; Overweight; Private schools